Pengaruh Motivasi dan Gaya Kepemimpinan terhadap Produktivitas Kerja Karyawan pada Perusahaan Cahaya Berlian - Yossi Hendriati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
Low labor productivity of employees in an organization or company is a symptom or problem that can cause the company is less stable because it can cause the unfulfillment of achievement of corporate goals. This study aims to analyze the influence of motivation and leadership style on employee productivity in company Cahaya Berlian. The population in this research is company Cahaya Berlian employees and the sample used is representative of the population with the number of 100 respondents by using nonprobability sampling technique in data collection. The results showed that the motivation and leadership style partially has significant effect on the performance of employees of company Cahaya Berlian. Key words:Motivation, Leadership style, Employee Productivity.